(3GdeeGQSGJ GdUajI deYdej eGOI GdYdhe heYdeGJgG hfhYjJgG hGdYhGed GdeDKQI ajgG ef GdUa GdQGHY Edi GdUa GdSGOS ef eQMdI GdJYdje GdCSGSj aj eOjfI HjQhJs - g ((3HjQhJs (3LGeYI GdbOjS jhSas, 2008)
(3JgOa gPg GdOQGSI Edi JMbjb GdCgOGa GdBJjI(B: 1) (3GdcTa Yf GdeeGQSGJ GdUajI deYdej eGOI GdYdhe heYdeGJgG ef GdUa GdSGOS ef eQMdI GdJYdje GdCSGSj(B. 2) (3JMOjO eGgjI gPg GdeeGQSGJ hfhYjJgG hGdYhGed GdJj JDKQ ajgG(B. 3) (3cTa CgejJgG aj GdYedjI GdJYdjejI(B- (3GdJYdejI(B. (3GYJeOJ GdOQGSI GdMGdjI GdefgL GdhUaj hGdefgL GdJMdjdj Gdcjaj(B. (3JVefJ GdYjfI GdJj GNJjQJ HGdWQjbI GdYThGFjI (B16 (3eOQSI ef cd GdeOGQS GdNGUI aj eOjfI HjQhJ GdJj JJVef Uaha GdMdbI GdKGfjI ef eQMdI GdJYdje GdCSGSj, Cj GdUa GdQGHY hGdNGeS hGdSGOS(B. (3ceG JCdaJ GdYjfI ef (B31 (3eYdkeG heYde jOqQShf eGOI GdYdhe aj Jdc GdeOGQS(B. (3Je JWHjb KdGK COhGJ dLeY GdeYdheGJ GddGReI dgPg GdOQGSI Ydi gPg GdYjfI hgj(B: (3GdGSJeGQI, Odjd GdebGHdI, Odjd GdeTGgOI GdUajI(B. (3ef CHQR GdfJGFL GdJj Je GdJhUd EdjgG HYO GdeYGdLI GdEMUGFjI ddOQGSI cGfJ ceG jdj(B: 1) (3Eqf GSJYeGd GdeYdejf ddCfTWI GdjOhjI hGdeNHQjI jYJeO HTcd eHGTQ Ydi YOO GdeJYdejf aj GdUa, EP JHjf Cf GdeYdejf GdPjf dOjge YOO bdjd ef GdeJYdejf aj GdUa jSJYedhf gPg GdCfTWI aj JOQjS eGOI GdYdhe CcKQ ef GdeYdejf GdPjf dOjge YOO cHjQ(B. 2) (3gfGc YdGbI EjLGHjI Hjf GdNdajI GdJQHhjI ddeYde (B((3MSH GdTgGOI GdLGeYjI hGdELGRI GdJYdjejI GdJj jMedgG(B)(3, hGdeSGYOI GdJj jbOegG efSb eGOI GdYdhe aj GdeOQSI hZjQg, JhGaQ GdehGO GdJYdjejI GdeSJYedI aj JYdje eGOI GdYdhe, cPdc YOO GdMUU, fhYjI GdcJGH GdeOQSj GdeSJYed aj JYdje eGOI GdYdhe(B. 3) (3YOe hLhO YdGbI EjLGHjI Hjf GdNHQI GdegfjI deYde eGOI GdYdhe, GdeJeKdI HYOO SfhGJ GdNHQI hGdOhQGJ GdJOQjHjI GdJj NVY dgG GdeYde(B. 4) (3Ef GdYhGed GdJj JDKQ aj eGgjI GdeeGQSGJ GdUajI deYde eGOI GdYdhe, Cj GdYhGed GdJj JLYd GdeYde jSJYed GdeeGQSGJ GdJbdjOjI Ch GdeeGQSGJ GdMOjKI gj(B: (3GdNdajI GdJQHhjI ddeYde, GdeSGYOI GdJj jbOegG efSb eGOI GdYdhe ddeYde, JhGaQ GdehGO GdJYdjejI, fhYjI GdcJGH GdeSJYed aj JYdje YOO GdeJYdejf aj GdUa hgPg GdMUU GdJj jOQSgG GdeYde aj GdCSHhY(B. 5) (3Ef SjGSI GdeOQSI GdJQHhjI JDKQ Ydi eGgjI GdeeGQSGJ GdUajI deYde eGOI GdYdhe(B. 6) (3Ef GdeYdejf GdPjf jSJYedhf GdeeGQSGJ GdHfGFjI aj JYdje eGOI GdYdhe, ge eJNUUhf aj WQGFb GdJYdje hdOjge GdeYQaI GdcGajI HcjajI GdJYdje(B.s
(3GdfhY (B: (3CWQhMIs
Keywords: Beirut; Beyrouth; Cycle primaire L$1 (Benseignement des Sciencess; Elementary Education Sciences education; Performance professionnel; Professional performance; (3GdGOGA Gdegfjs; (3GdeQMdI GdGHJOGFjI JYdje GdYdhes; (3HjQhJs